Analisis Manajemen Risiko Keuangan pada UMKM Lela Florist Kota Semarang - Ninik Dwi Atmini; Umi Fadlilah Hidayanti; Yoki Nawan Gunara (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
SMES (Micro, Small and Medium Enterprises) often face significant challenges, especially related to financial and workforce risk management. This research aims to analyze Lela Florist's financial risk management. In this research, a descriptive qualitative approach with interviews was used to collect data from business owners and female employees. The analysis is carried out with a focus on financial risk management strategies, such as product and service diversification, creative promotions, cash flow management, separation of company assets and access to capital. Lela Florist has implemented various strategies to manage financial risks effectively. Diversification of products and services, creative promotions, and utilization of online delivery and ordering services help reduce financial risks and maintain revenue stability. Meanwhile, efficient management of employee costs, employee development and effective performance management increases productivity and maintains service quality. This research shows that Lela Florist's financial risk management has effectively played an important role in the operational success of SMES.